Molecular Disorganization of Axons Adjacent to Human Cortical Microinfarcts - Coban, Hamza; Tung, Spencer; Yoo, Bryan; Vinters, Harry V.; Hinman, Jason D. (Frontiers in Neurology, 2017)
Cortical microinfarcts are microscopically identified wedge shaped ischemic lesions that occur at or near the cortical surface and result from occlusion of penetrating arterioles. These microscopic lesions can be observed with high-resolution magnetic resonance imaging in aging brains and in patients with cerebrovascular disease (CVD). Recent studies have suggested that strategically located microinfarcts strongly correlate with cognitive deficits, which can contribute to Alzheimer’s Disease (AD) as well as other forms of dementia. We have recently shown that the molecular organization of axons into functional microdomains is altered in areas adjacent to white matter lacunar and microinfarcts, creating a peri-infarct penumbral injury in surviving axons. In this study, we hypothesized that similar changes were present in nodal, paranodal, and axon initial segments adjacent to human cortical microinfarcts. Paraffin-embedded sections of autopsy brain tissue from five patients with cortical microinfarcts were immunofluorescently labeled for nodal and paranodal markers including beta-IV spectrin, ankyrin-G, and contactin-associated protein (caspr). High magnification images from the peri-infarct cortical tissue were generated using confocal microscopy. In surviving cortical tissue adjacent to microinfarcts, we observed a dramatic loss of axon initial segments, suggesting that neuronal firing capacity in adjacent cortical tissue is likely compromised. In addition, the number of identifiable nodal/paranodal complexes in surviving cortical tissue is reduced adjacent to microinfarcts, while the average paranodal length is increased indicating a breakdown of axoglial contact. This axonal microdomain disorganization occurs in the relative absence of changes in the structural integrity of myelinated axons as measured by myelin basic protein and neurofilament staining. These findings indicate that the molecular organization of surviving axons adjacent to human cortical microinfarcts is abnormal, reflecting lost axoglial contact and the functional elements necessary for neural transmission. This study provides support for the concept of a microinfarct penumbral injury that may account for the cumulative cognitive effect of these tiny strokes.